Cost Effectiveness Analysis of Fecal Transplant Delivery Methods for Recurrent Clostridium difficile Infections in Outpatients. (4th October 2017) - Walker, Jeremey; Gundacker, Nathan; Rodriguez, Martin; Eaton, Ellen
Abstract: Background: Clostridium difficile infection (CDI) accounts for more than 1 billion annually in US health care costs. Recurrent CDI (RCDI, recurrence within 8 weeks of initial treatment) contributes substantially to this cost. The objective of the study was to compare the cost effectiveness of FMT delivered via colonoscopy vs. blind nasogastric tube (NGT) in outpatients. We hypothesized that FMT by NGT would be cost-effective given its low risk and simplicity. Methods: A decision-analytic simulation model compared the cost effectiveness of FMT by colonoscopy vs. NGT from a third-party payer perspective. Our base case cure rates were derived from a cohort receiving outpatient RCDI treatment at our institution. Cure was defined as resolution of symptoms for ≥ 90 days. Procedural cost and consultation was defined by average reimbursement to a large southeastern medical center in 2016 USD based on current procedural terminology (CPT) codes, and cost of disease states were derived from published literature. Health utilities were defined by quality of life year (QALY) based on published literature. Incremental Cost Effectiveness ratio (ICER) was defined as the cost per additional QALY gained. We assumed a 90 day time horizon. One-way sensitivity analysis was performed on all variables using ranges defined by published literature. We used TreeAge Software (Williamstown, MA). Results: In the base case, FMT by colonoscopy was dominant (more effective and less costly) than NGT, with cost of 1, 568/QALY vs. 1, 910/QALY respectively. Cure rates of FMT by colonoscopy vs. NGT (100% vs. 87%) had the largest impact on ICER based on one-way sensitivity analysis. Therefore, a subsequent two-way sensitivity analysis was conducted to compare cure rates of both delivery methods and found that NGT delivery is cost effective as cure rates approach colonoscopy delivery cure rates within 5 percentage points. Conclusion: Contrary to our hypothesis, our decision model supports FMT by colonoscopy as the preferred delivery method in outpatients with RCDI relative to NGT delivery. Additional costs of colonoscopy delivery are off-set by the improved cure rate leading to lower overall costs. As cure rates from NGT delivery are optimized, NGT may become the preferred method for FMT delivery. Disclosures: All authors: No reported disclosures.